Research on the Basic Framework and Construction of Intelligent Financial Sharing Platform - Yonghong Cai, Siwen Yu, Xinna Zheng (Forest Chemicals Review, 1970)
With the rapid change of information technology and sharing the high speed development of economy, the increasingly fierce competition between enterprises, in order to deal with the new change, enterprises should improve their comprehensive management level, ensure the advantages in the market competition, intelligent financial sharing platform can promote the enterprise financial management level, the rapid reaction to market changes, improve enterprise in the market competition advantage. This paper discusses the potential real-world applications that intelligent financial management platforms can bring to corporate management, in order to construct the framework of intelligent financial sharing platform from two aspects of financial accounting and management accounting, and puts forward feasible construction suggestions.